FOREIGN EXCHANGE MARKETS AND OPERATIONS IN THE CONTEXT OF DIGITALIZATION - J. Konopleva; O. Pakova; K. Gavrilov (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the theoretical foundations of the functioning of currency markets. Classification of types of currency transactions according to the legislation of the Russian Federation is given. The article highlights the impact of financial globalization on the Russian currency market. The article considers the trends that take place in the foreign exchange market in modern conditions of digitalization. The article focuses on the accelerated development of digital currencies in modern conditions, including the review of the «Digital ruble «Report prepared by the Central Bank of the Russian Federation for public consultations, which reflects the main prerequisites for creating a domestic digital currency.